Discipline: The Canonical Buddhism of the Vinayapitaka - Pandiyappallil, Joseph (Journal of Dharma, 1984)
John C. Holt Discipline: The Canonical Buddhism of the Vinayapitaka Delhi: Motilal Banarsidass, 1981, pp. ix, + 157. Rs. 50/-